Flood Disaster Risk Mapping with Geographic Information Systems Dan Makham Tia District, Kanchanaburi Province - Sriboonruang, Komsan; Kumkrua, Malinee; Jaikaew, Pantipa (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2022)
This research had objectives in this study were; 1) To study the flooding disaster risk in Dan Makham Tia District from The Geographic Information Systems and 2) To analyze the vulnerable areas on flooding in Dan Makham Tia District from the Geographic Information System. This research used research tools include interviews and a vulnerability factor survey. The population and the samples group consisted of officers of the Local Government Organization in Dan Makham Tia District, Volunteer for disaster prevention and mitigation in the area, Disaster Victims' households and the rescue groups in the area using the Potential Surface Analysis (PSA) and The Risk Assessment using risk matrix tables. The risk studies were shown as a percentage value. The results showed that: The disaster risk in Dan Makham Tia District from the Geographic Information System resulted in two conclusions as follows: First issue, the flood risk map from geographic information system. The results of the study are as follows; the high risk flooding areas account for 29.40 percent and the area most risks to flooding found scattered throughout on the plains accounted for 42.20 percent. The Second issue; The map of vulnerability to floods consider the effects of the risk factors and flood adaptation capacity of households. The overall analysis of vulnerability shows that 1 household has a high level of vulnerability to flooding and 27 households that are vulnerable to flooding at a moderate level. The research results have led to an upgrade in flood management, thus creating an action plan for using maps to develop the capacity of local administrative organizations, namely pre-disaster, during the disaster, and post-disaster action plans of the local government organization in Dan Makham Tia District, Kanchanaburi.